Factor completely.
n 2 + 7n - 44
(n - 4)(n - 11)
(n - 4)(n + 11)
(n + 4)(n - 11)

n^2 + 7n - 44 = (n + 11)(n - 4)

s

Question

Asked 11/14/2014 9:55:37 AM

Updated 11/16/2014 10:12:27 PM

1 Answer/Comment

Rating

8

n^2 + 7n - 44 = (n + 11)(n - 4)

Added 11/16/2014 10:12:27 PM

This answer has been confirmed as correct and helpful.

Confirmed by yumdrea [11/16/2014 10:15:31 PM]

The height of a triangle is 4 more than the base, and the area of the triangle is 6 square units. Find the length of the base. Let x = the length of the base **Weegy:** Let x = the length of the base, the height is x + 4. its area = 1/2x(x + 4) = 6, x^2 + 4x - 12 = 0, (x + 6)(x - 2) = 0, x = -6 or x = 2. So the base is 2 units. (More)

Question

Expert Answered

Updated 11/18/2014 11:15:12 AM

0 Answers/Comments

Solve n3 + 2n2 - 15n = 0 by factoring. Show the factored form of the equation, and the resulting solutions.
**Weegy:** n3 2n2 - 15n = 0 is n (2 n^4-15) = 0.
(More)

Question

Updated 11/18/2014 9:04:32 PM

1 Answer/Comment

n^3 + 2n^2 - 15n = 0

n(n^2 + 2n - 15) = 0

n(n + 5)(n - 3) = 0

n = 0

n + 5 = 0, n = -5

n - 3 = 0, n = 3

So the solutions are n = 0 , n = -5 , n = 3 .

n(n^2 + 2n - 15) = 0

n(n + 5)(n - 3) = 0

n = 0

n + 5 = 0, n = -5

n - 3 = 0, n = 3

So the solutions are n = 0 , n = -5 , n = 3 .

Added 11/18/2014 9:04:32 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [11/18/2014 9:10:18 PM]

34,460,732

questions answered

S

L

1

1

1

1

1

1

1

1

1

1

1

1

1

1

1

1

1

P

1

L

P

1

Points 753 [Total 6626] Ratings 15 Comments 603 Invitations 0 Offline

There are no comments.